Immature teratoma of the urinary bladder - Indriwati, Indriwati (Universitas Gadjah Mada, 2003)
A three year old female with immature teratoma of the urinary bladder was reported. The cell differentiation theory should be considered as an important alternative theory in the histogenesis of extragonadal immature teratoma. Extragonadal immature teratoma can be differentiated from extrarenal Wilms tumor by a proper histopatological examination particularly in view of the presence of neuroepithelial tissue.Key words : bladder immature teratoma - extrarenal Wilms tumor -cell dedifferentiation theory